Implementasi Diversi terhadap Anak Sebagai Pelaku Tindak Pidana Kecelakaan Lalu Lintas di Kepolisian Resor Jember dari Tahun 2022 sampai Tahun 2024 Berdasarkan Perspektif Hukum Positif dan Hukum Islam: Implementation of Diversion for Children as Perpetrators of Traffic Accidents at the Jember Police Resort from 2022 to 2024 Based on Positive Law and Islamic Law Perspectives - Moch Niko Unnaso’I; Dwi Hastuti (CLEAR: Criminal Law Review, 2025)
There are research focuses in this thesis, namely: 1) What is the role of the Jember Resor Police in implementing diversion of children as perpetrators of traffic accident crimes based on a positive legal perspective? 2) What are the factors that hinder the implementation of diversion against children as perpetrators of traffic accidents in the Jember Resor Police? 3) How is the implementation of diversion against children as perpetrators of traffic accident crimes based on the perspective of Islamic law? This study uses an empirical legal research method, by combining a sociological approach to law with a legislative approach.The results of this study are: 1. The role of the Jember Resor Police in implementing diversion against children as perpetrators of traffic accident crimes, the police are involved in the mediation process, if an agreement is reached, a restorative justice approach is carried out. However, if mediation does not work, then a diversion process will be carried out. 2. Judging from the inhibiting factors based on law enforcement in the Jember Resor Police, based on the legal structure, lies in the complaint offense, and in the substance of the law, the obstacle lies in the diversion conditions that are not specifically mentioned. However, the SPPA Law mentions what needs to be taken into account and considered in the diversion process, as well as in the legal culture of obstacles that occur due to the lack of legal awareness in society. And the obstacle to the diversion process is regarding the absence between the two parties to the Satlantas office due to distance and incorrect assumptions regarding the long handling and the cost that is spent. 3. If viewed from the perspective of Islamic law, that traffic accidents are not regulated specifically but this diversion effort is also called As-shulhu which means peace, and for the actions given to the child who commits the crime, the act of ta'dib is given, namely education whose punishment is to give lessons which do not affect the child's psyche and the suitability of Islamic law and positive law prioritizes case to restorative justice process. Terdapat fokus penelitian dalam skripsi ini, yaitu: 1) Bagaimana peran Kepolisian Resor Jember dalam mengimplementasikan diversi terhadap anak sebagai pelaku tindak pidana kecelakaan lalu lintas berdasarkan perspektif hukum positif? 2) Apa saja faktor yang menghambat pelaksanaan diversi terhadap anak sebagai pelaku tindak pidana kecelakaan lalu lintas di Kepolisian Resor Jember? 3) Bagaimana implementasi diversi terhadap anak sebagai pelaku tindak pidana kecelakaan lalu lintas berdasarkan perspektif hukum Islam? Penelitian ini menggunakan metode penelitian hukum empiris, dengan memadukan pendekatan sosiologis hukum dan pendekatan perundang-undangan. Hasil penelitian ini adalah: 1. Peran Kepolisian Resor Jember dalammengimplementasikan diversi terhadap anak sebagai pelaku tindak pidana kecelakaan lalu lintas, yaitu polisi terlibat dalam proses mediasi. Jika tercapai kesepakatan, maka dilakukan pendekatan keadilan restoratif. Namun, apabila mediasi tidak berhasil, maka dilanjutkan ke proses diversi. 2. Jika ditinjau dari faktor penghambatnya berdasarkan penegakan hukum di Kepolisian Resor Jember, pada struktur hukumnya hambatan terletak pada sifat delik aduan, sedangkan pada substansi hukumnya hambatan terletak pada syarat diversi yang tidak disebutkan secara spesifik. Namun, dalam Undang-Undang SPPA disebutkan hal-hal yang perlu diperhitungkan dan dipertimbangkan dalam proses diversi. Pada aspek kultur hukum, hambatan muncul karena rendahnya kesadaran hukum masyarakat. Hambatan lain dalam proses diversi yaitu ketidakhadiran kedua belah pihak di kantor Satlantas karena jarak serta anggapan yang keliru mengenai penanganan yang lama dan biaya yang besar. 3. Jika ditinjau dari perspektifhukum Islam, kecelakaan lalu lintas tidak diatur secara spesifik, namun upaya diversi ini disebut As-shulhu yangberarti perdamaian. Terhadap anak pelaku diberikan tindakan ta’dib, yaitu pendidikan dengan hukuman yang bersifat memberi pelajaran tanpa memengaruhi kejiwaan anak. Dengan demikian, baik hukum Islam maupun hukum positif samasama mengutamakan penyelesaian melalui keadilan restoratif.